Previous Musical Experience and Cortical Thickness Relate to the Beneficial Effect of Motor Synchronization on Auditory Function - Merten, Natascha; Kramme, Johanna; Breteler, Monique M. B.; Herholz, Sibylle C. (Frontiers in Neuroscience, 2019)
Auditory processing can be enhanced by motor system activity. During auditory-motor synchronization, motor activity guides auditory attention and thus facilitates auditory performance through active sensing. Previous research on enhanced auditory processing through motor synchronization has been limited to easy tasks with simple stimulus material. Further, the mechanisms and brain regions underlying this synchronization are unclear. We investigated the effect of motor synchronization on auditory performance with naturalistic, musical auditory material in a discrimination task. We further assessed how previous musical training and cortical thickness of specific brain regions relate to different aspects of auditory-motor synchronization. We conducted an auditory-motor experiment in 139 adults. The task involved melody discrimination and beat tapping synchronization. Additionally, 68 participants underwent structural MRI. We found that individuals with better auditory-motor synchronization accuracy showed improved melody discrimination, and that melody discrimination was better in trials with higher tapping accuracy.. However, melody discrimination was worse in the tapping than in the listening only condition. Longer previous musical training and thicker Heschl’s gyri were associated with better melody discrimination and better tapping synchrony. Post-hoc analyses furthermore pointed to a possible moderating role of frontal regions. Our results suggest that motor synchronization can enhance auditory discrimination abilities through active sensing, but that this beneficial effect can be counteracted by dual-task inference when the two tasks are too challenging. Moreover, prior experience and structural brain differences influence the extent to which an individual can benefit from motor synchronization in complex listening. This could inform future research directed at development of personalized training programs for hearing ability.